Will the Import Ban Prove Effective? (The Pakistan Development Review, 2025)
Pakistan has for decades now been facing a financing crisis. The expenditures have always remained significantly higher than the revenues making the governments look to various sources to finance this gap. One major reason for the country’s lackluster performance in managing its expenses stems from the import dependency of the economy. Not only do we import the raw materials for our industries, but the local demand for commodities, agricultural and manufactured, is met through imports. While Pakistan’s import per capita remains lower than other regional countries, the low export value which has remained rather stagnant over years is a major cause of concern. Figure 1 below depicts Exports and Imports of Pakistan during the last decade.